Extrapolating Terminology: The Carnivalesque Practice of Language Writing In the Grotesque Body of I Don’t Have Any Paper - Milman, David (Pivot: A Journal of Interdisciplinary Studies and Thought, 2013)
There is a similarity between the rhetorical strategies of Language Writing and the rhetorical strategies attributed to carnivalesque texts by Mikhail Bakhtin. However, the aesthetic differences between standard uses of the carnivalesque and grotesque realism may, at first, obfuscate these similarities in rhetorical strategy. While the aesthetic of these two forms of writing is certainly not identical, there are enough allegorically and rhetorically parallel elements to state that a form of the carnivalesque and grotesque is at work in Language Writing. To prove as much I will summarize Mikhail Bakhtin’s articulation of carnival and grotesque realism and then draw lines of similarity between that articulation and the strategies of Language Writing expressed by Bruce Andrews and Steve McCaffery. In the process I will bolster my argument with reference to textual examples, taken from Bruce Andrews I Don’t Have Any Paper, which exemplify these parallels in operation.